SPASIAL CLASIFICATION MINING UNTUK MENENTUKAN PRAKIRAAN CURAH HUJAN BERDASARKAN KARAKTERISTIK WILAYAH - Eva Khudzaeva (UIN Syarif Hidayatullah Jakarta, 2016)
Information about the condition of rainfall is one of the essential elements and a big influence on all kinds of livelihood activities, Banten province is a region that is characteristic of the region vary, so study the spatial patterns of the relationship between rainfall data with the characteristics of the region, will obtain the factors that influence precipitation and can determine the bulk rainfall prediction based on its characteristics in Banten Province. Data mining provides the desired search patterns in large databases to assist in decision making at a time when it comes to looking for patterns of relatedness in the used mining methods using decision tree classification, where the rainfall data will be classified with regional characteristics, so as to generate a forecast of rainfall.